Effects of the MDM-2 inhibitor Nutlin-3a on PDAC cells containing and lacking WT-TP53 on sensitivity to chemotherapy, signal transduction inhibitors and nutraceuticals. (May 2019) - Candido, Saverio; Abrams, Stephen L.; Steelman, Linda S.; Lertpiriyapong, Kvin; Martelli, Alberto M.; Cocco, Lucio; Ratti, Stefano; Follo, Matilde Y.; Murata, Ramiro M.; Rosalen, Pedro L.; Bueno-Silva, Bruno; de Alencar, Severino Matias; et al.
Abstract: Mutations at the TP53 gene are readily detected (approximately 50–75%) in pancreatic ductal adenocarcinoma (PDAC) patients. TP53 was previously thought to be a difficult target as it is often mutated, deleted or inactivated on both chromosomes in certain cancers. In the following study, the effects of restoration of wild-type (WT) TP53 activity on the sensitivities of MIA-PaCa-2 pancreatic cancer cells to the MDM2 inhibitor nutlin-3a in combination with chemotherapy, targeted therapy, as well as, nutraceuticals were examined. Upon introduction of the WT- TP53 gene into MIA-PaCa-2 cells, which contain a TP53 gain of function (GOF) mutation, the sensitivity to the MDM2 inhibitor increased. However, effects of nutlin-3a were also observed in MIA-PaCa-2 cells lacking WT-TP53, as upon co-treatment with nutlin-3a, the sensitivity to certain inhibitors, chemotherapeutic drugs and nutraceuticals increased. Interestingly, co-treatment with nutlin-3a and certain chemotherapeutic drug such as irinotecan and oxaliplatin resulted in antagonistic effects in cells both lacking and containing WT-TP53 activity. These studies indicate the sensitizing abilities that WT- TP53 activity can have in PDAC cells which normally lack WT- TP53, as well as, the effects that the MDM2 inhibitor nutlin-3a can have in both cells containing and lacking WT-TP53 to various therapeutic agents.